Application of blockchain and big data technology in the safety information management of architecture employees. Issue 1 (September 2020) - Wei, Yinshang; Cui, Enwei
Abstract: In the traditional data management of safety information for construction workers, each department independently manages and uploads data. It is difficult to share data and the utilization rate of worker safety information is low. In response to this problem, a safety information management model for construction workers based on blockchain and big data technology is proposed. This model is based on the characteristics of the blockchain to record data, which completely changes the data collection, data processing and analysis, and data storage modes and methods, and records the entire process of safety-related data and information of construction employees during their work. Build a complete personal safety information chain, which truly reflects the safety literacy of employees, and establish a safety quality information storage evaluation system for coal mine employees. This model can provide real and effective safety information for construction safety management and promote personnel matching.